Penguatan Penguasaan Kosakata Bahasa Inggris bagi Santri Rumah Qur’an Bani Khamta melalui Pembelajaran Berbasis Teknologi Digital - Marshanda Marshanda; Raysha Ramadhani; Muhammad Dicky Setiawan; Zaitun Qamariah; Hesty Widiastuty; Aris Sugianto (Universitas Pahlawan Tuanku Tambusai, 2026)
Low motivation and engagement among beginner-level santri in learning English in non-formal educational settings have become challenges in mastering English vocabulary. This community service program aimed to improve the vocabulary size of santri at Rumah Qur’an Bani Khamta through digital technology-based English learning using YouTube, Canva, and Kahoot. The implementation method used direct practice targeting early-age santri. The activities were carried out through the introduction of basic vocabulary materials, the use of educational videos, Canva-based worksheets, and Kahoot interactive quizzes. Evaluation was conducted through observation of the students’ participation, enthusiasm, and responses during the learning process. The results showed that the use of digital media and gamification was able to increase the santri’s enthusiasm, active participation, and self-confidence in using English. This program had a positive impact on improving vocabulary size and creating a more interactive, enjoyable, and meaningful learning environment.